2021
DOI: 10.1111/eci.13718
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen β chain and FXIII polymorphisms affect fibrin clot properties in acute pulmonary embolism

Abstract: Background Prothrombotic fibrin clot properties, including increased clot density, are in part genetically determined. We investigated whether fibrinogen alpha‐chain gene (FGA) c.991A>G (rs6050), fibrinogen beta chain gene (FGB) −455G>A (rs1800790) and factor XIII gene (F13) c.103G>T (rs5985) polymorphisms affect plasma fibrin clot properties in patients with acute pulmonary embolism (PE). Methods As many as 126 normotensive patients with PE, free of cancer, were genotyped by TaqMan assay. Fibrin clot permeabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Failure of timely dissolution of PE can result in chronic thromboembolic pulmonary hypertension, right heart failure, and cardiogenic shock. 118 Clinical observations [119][120][121][122][123] and experimental studies with mice [124][125][126] support roles for both fibrin(ogen) and FXIII(a) in maintaining venous thrombus stability and preventing embolization.…”
Section: Fibrin and Fxiiia As Determinants Of Venous Thrombus Formati...mentioning
confidence: 97%
See 2 more Smart Citations
“…Failure of timely dissolution of PE can result in chronic thromboembolic pulmonary hypertension, right heart failure, and cardiogenic shock. 118 Clinical observations [119][120][121][122][123] and experimental studies with mice [124][125][126] support roles for both fibrin(ogen) and FXIII(a) in maintaining venous thrombus stability and preventing embolization.…”
Section: Fibrin and Fxiiia As Determinants Of Venous Thrombus Formati...mentioning
confidence: 97%
“…120,121,[128][129][130][131] The fibrinogen β chain (FGB [rs1800790]) and FXIII Val34Leu polymorphisms have been implicated as determinants of altered clot properties in acute PE. 123 Using intravital video microscopy and lung histology of a FeCl 3 -induced model of acute thrombosis, Gross and co-workers found reduced thrombus stability and increased emboli in mice treated with the direct thrombin inhibitor dabigatran and in FXIII-deficient mice, leading to the hypothesis that by reducing thrombin production, anticoagulant treatment reduces activation of FXIII and the thrombin-activatable fibrinolysis inhibitor and decreases thrombus stability. 132 They subsequently showed that supplementation with FXIII stabilizes venous thrombi and decreases embolization without altering thrombus size.…”
Section: Fibrin and Fxiiia As Determinants Of Venous Thrombus Formati...mentioning
confidence: 99%
See 1 more Smart Citation
“…PE is often categorized together with deep vein thrombosis (DVT) as venous thromboembolism (VTE), and they both share common risk factors, including venous stasis, hypercoagulability, and endothelial damage. Two large-scale genome-wide association studies (GWASs) have identified 34 and 22 independent genetic signals associated with VTE risk [ 7 , 8 ], primarily involving loci related to coagulation and fibrinolytic, respectively [ 9 , 10 ]. In addition, circulating cytokines, blood pressure and blood metabolites have been linked to an increased risk of VTE [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the fibrinogen gene, particularly the transition from guanine to adenine at nucleotide 455 of the beta-fibrinogen promoter, lead to elevated fibrinogen levels. Furthermore, the −455 G>A variant has been identified as a risk factor for fibrin clot formation in PE cases [ 10 ] and predisposes to coronary artery disease, as well as cerebral infarction [ 11 , 12 ]. So far, in MS animal models, thrombin and fibrin(ogen) have been detected in pre-demyelinated CNS areas, attracting resident and infiltrating immune cells from the periphery, contributing further in abnormal BBB permeability, and stimulating the inflammatory process [ 13 ].…”
Section: Introductionmentioning
confidence: 99%